2024
DOI: 10.2196/53559
|View full text |Cite
|
Sign up to set email alerts
|

The Temperature Feature of ChatGPT: Modifying Creativity for Clinical Research

Joshua Davis,
Liesbet Van Bulck,
Brigitte N Durieux
et al.

Abstract: More clinicians and researchers are exploring uses for large language model chatbots, such as ChatGPT, for research, dissemination, and educational purposes. Therefore, it becomes increasingly relevant to consider the full potential of this tool, including the special features that are currently available through the application programming interface. One of these features is a variable called temperature, which changes the degree to which randomness is involved in the model’s generated output. This is of part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Additionally, a limitation of this study is the lack of temperature control, which can influence the results. Studies have shown that adjusting the "creativity" settings of Chat-GPT, which involves varying the temperature settings, has potential applications for clinicians [38]. Future research should incorporate temperature regulation to evaluate its effect on study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a limitation of this study is the lack of temperature control, which can influence the results. Studies have shown that adjusting the "creativity" settings of Chat-GPT, which involves varying the temperature settings, has potential applications for clinicians [38]. Future research should incorporate temperature regulation to evaluate its effect on study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the stochastic nature of these tools can result in scenarios where the identical version of a tool, prompted in the same manner, still fails to yield consistent output across replications. There have been attempts to increase the replicability of outcomes (e.g., by controlling the model's settings; Davis et al, 2024), yet there is need for more research and investigation on reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…The 'temperature' parameter balances ChatGPT's exploratory and conservative response capabilities, directly influencing the randomness of its responses. A higher temperature results in more random and creative responses, while a lower temperature leads to more deterministic outputs 21 . For each temperature setting, experiments were also performed using three different random seeds.…”
Section: Reasoningmentioning
confidence: 99%